Analysis of factors influencing dengue prevention KAP among urban residents in Guangzhou and evaluation of mHealth intervention effects - Huang, Zhihui; Li, Zhaohong; Li, Lifen; Wu, Shiqi; Chen, Changming; Li, Nengjiu; Lu, Jianyun (Frontiers in Public Health, 2025)
ObjectiveThis study aims to analyze the factors influencing dengue fever prevention knowledge, attitude, and practice (KAP) among urban residents in Guangzhou and to evaluate the effectiveness of an mHealth intervention based on the KAP model.MethodsA cross-sectional study was conducted with 3,571 participants from an online survey. A quasi-experimental study (84 in the intervention group and 83 in the control group) was carried out over 2 months. Electronic questionnaires assessed baseline KAP levels, and the groups’ differences were compared post-intervention.ResultsThe baseline survey revealed a knowledge awareness rate of 80.29%, with the lowest levels found in males aged 55 and above, low-education groups, and temporary housing residents. Significant demographic differences were observed in prevention motivation and behavior (p < 0.05). Post-intervention, the experimental group showed significant improvements in knowledge scores (p < 0.05), but no significant differences were found in prevention motivation (13.26 ± 1.92 vs. 13.32 ± 2.02) and behavior (4.08 ± 1.00 vs. 4.34 ± 0.91) (p > 0.05).ConclusionThe mHealth intervention effectively improved knowledge, but had limited impact on belief formation and behavior change. Future interventions should integrate community-specific strategies to enhance behavioral change mechanisms.